2021
DOI: 10.3390/geriatrics6010028
|View full text |Cite
|
Sign up to set email alerts
|

Association between Levels of Physical Activity, Sarcopenia, Type 2 Diabetes and the Quality of Life of Elderly People in Community Dwellings in Lebanon

Abstract: There is a lack of data from developing countries on the link between physical activity (PA) on health outcomes. This study examines the association between the level of PA and sarcopenia, cardiovascular risk factors (i.e., dyslipidemia, type 2 diabetes (T2D), and cardiovascular diseases), and the health-related quality of life (HRQoL) among elderly people, in community dwellings in Lebanon. In this cross-sectional, observational study, body composition, levels of PA, and the HRQoL of 243 elderly people living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…This might reflect that female individuals are more compliant with their cancer screening recommendations than male individuals (17,18). At an average age of 63.9 years, the prevalence of hypertension and diabetes mellitus in our population is similar to other studies done in Lebanon, while the prevalence of dyslipidemia was almost twice as high (19)(20)(21).…”
supporting
confidence: 85%
“…This might reflect that female individuals are more compliant with their cancer screening recommendations than male individuals (17,18). At an average age of 63.9 years, the prevalence of hypertension and diabetes mellitus in our population is similar to other studies done in Lebanon, while the prevalence of dyslipidemia was almost twice as high (19)(20)(21).…”
supporting
confidence: 85%
“…This can be explained by 46.2% of older adults reported physical activity twice or more of week. Several studies have shown that physical activity is associated with a lower prevalence of sarcopenia (25)(26)(27)(28)(29). A study conducted among Japanese communitybased older adults demonstrated that 7% were sarcopenic by AWGS criteria (30).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Physical exercise helps prevent the metabolic syndrome in the elderly and reduces the risk of type 2 diabetes. Saadeddine D et al [ 22 ] collected data on the lack of links between PA and health outcomes in developing countries. They conducted a cross-sectional survey to study the relationship between the PA level of middle-aged and elderly people in community housing in Lebanon and skeletal muscle reduction, cardiovascular risk factors (dyslipidemia, type 2 diabetes, and cardiovascular disease), and quality of life.…”
Section: Discussionmentioning
confidence: 99%